National Health Information Network: Lessons Learned From the USA and the UK - Moghaddasi, Hamid; Rabiei, Reza; Asadi, Farkhondeh; Mohammadpour, Ali (Archives of Advances in Biosciences, 2017)
National Health Information Network (NHIN) is a network in which all health care organizations, government agencies and other health-related organizations are connected to each other to exchange information about health. Due to the necessity of a framework for NHIN development, in this paper, according to the literature review, a definition for NHIN framework was provided, and then the NHIN related projects were reviewed in the United States of America (USA) and the United Kingdom (UK), NHIN and National Programme for Information Technology in the NHS (NPfIT), respectively. The Review of NHIN framework in the countries studied show some similarities and differences in each dimension that are discussed in this framework. NHIN guiding principles in the NHS NPfIT were not regarded or were considered incomplete, compared to the US. NHIN architecture in the US is decentralized while it is centralized in the UK. Based on the review of NHIN framework, these two countries represent important points that can be used in many other countries. However, it can be said that the development of NHIN does not only mean the implementation of national system or systems, or the binding of local health information systems, but It also needs to build on a framework in which many of the issues related to the formation of NHIN would be considered; including the cooperation between government, private sector and stakeholders with regard to local, national and international needs.